下颌骨原发腺泡细胞癌1例 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2018)
Acinic cell carcinoma is a relatively rare salivary gland tumor predominantly occurring in the major glands. Therefore, acinic cell carcinoma rarely occurs in the mandible. In this study, a case of primary acinic cell carcinoma of the mandible was reported, and relevant literature was reviewed. The etiology, clinical symptom, image and histological features, diagnosis, treatment, and prognosis of acinic cell carcinoma in the mandible were discussed.